Achieving an Ohmic contact in graphene-based van der Waals heterostructures by intrinsic defects and the inner polarized electric field of Janus AlGaSSe. (2nd November 2021) - Wang, Jiaming; Zhang, Dongxue; Zhou, Baozeng
Abstract : The Schottky barrier height is mainly affected by the synergistic action of the inner polarization electric field of Janus AlGaSSe and the 2D/2D heterostructure. Abstract : The formation of graphene-based van der Waals heterostructures has shown great potential for designing novel electronic and optoelectronic nanodevices. However, the Schottky barrier generated by the contact between a semimetal (graphene) and a semiconductor hinders the conduction of electrons. Thus, it is necessary to effectively adjust the Schottky barrier height using an intrinsic or an external electric field and form a low-resistance Ohmic contact. For addressing this problem, motivated by the successful synthesis of the Janus monolayer, which has an intrinsic inner polarized electric field, we systematically investigate the electronic structure and interfacial characteristics of a Janus AlGaSSe/graphene heterostructure by using first-principles simulations. The inner polarized electric field of the quaternary AlGaSSe can be enhanced in a synergistic manner by polarized substitution of cations and anions. We found that the Janus AlGaSSe and graphene could form a stable van der Waals heterostructure and the intrinsic electronic properties are well preserved. The different polarized substitution (cations or anions) can effectively regulate the barrier height of the heterostructure and an n-type Schottky contact with a smallest Schottky barrier height of 0.24 eV formed at the graphene/SGaAlSe interface, which is mainly affected by the inner polarized electric field of Janus AlGaSSe and can be further optimized to an Ohmic contact by intrinsic defects without inducing any structural damage to the graphene channel. Moreover, the vertical strain and electric field can also be effectively used to tune both the contact types and the Schottky barrier height. Our results may provide useful information for designing novel, high-performance electronic and optoelectronic devices based on van der Waals heterostructures.